An open source heterogeneous 3D printed mouse phantom utilising a novel bone representative thermoplastic. (29th May 2020) - Price, Gareth; Biglin, Emma R; Collins, Sean; Aitkinhead, Adam; Subiel, Anna; Chadwick, Amy L; Cullen, David, M; Kirkby, Karen J; Schettino, Giuseppe; Tipping, Jill; Robinson, Andrew
Abstract: The lack of rigorous quality standards in pre-clinical radiation dosimetry has renewed interest in the development of anthropomorphic phantoms. Using 3D printing customisable phantoms can be created to assess all parts of pre-clinical radiation research: planning, image guidance and treatment delivery. We present the full methodology, including material development and printing designs, for the production of a high spatial resolution, anatomically realistic heterogeneous small animal phantom. A methodology for creating and validating tissue equivalent materials is presented. The technique is demonstrated through the development of a bone-equivalent material. This material is used together with a soft-tissue mimicking ABS plastic filament to reproduce the corresponding structure geometries captured from a CT scan of a nude mouse. Air gaps are used to represent the lungs. Phantom validation was performed through comparison of the geometry and x-ray attenuation of CT images of the phantom and animal images. A 6.6% difference in the attenuation of the bone-equivalent material compared to the reference standard in softer beams (0.5 mm Cu HVL) rapidly decreases as the beam is hardened. CT imaging shows accurate (sub-millimetre) reproduction of the skeleton (Distance-To-Agreement 0.5 mm ± 0.4 mm) and body surface (0.7 mm ± 0.5 mm). Histograms of the voxel intensity profile of the phantom demonstrate suitable similarity to those of both the original mouse image and that of a different animal. We present an approach for the efficient production of an anthropomorphic phantom suitable for the quality assurance of pre-clinical radiotherapy. Our design and full methodology are provided as open source to encourage the pre-clinical radiobiology community to adopt a common QA standard. Abbreviations: ABS – acrylonitrile butadiene styrene, CBCT – cone beam computed tomography, FDM – fused deposition modelling, HVL – half value layer, HU – Hounsfield units, ICRU - International Commission on Radiation Units and Measurements, NIST – National Institute of Standards and Technology, NPL – National Physical Laboratory, QA – quality assurance, ROI – region of interest, SARRP – small animal radiation research platform, STL – stereolithography.